2019
DOI: 10.4103/jfmpc.jfmpc_446_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,25 dihydroxy vitamin D3 supplementation on pain relief in early rheumatoid arthritis

Abstract: Background:To assess effect of 1,25 dihydroxy vitamin D3 supplementation on pain relief in early rheumatoid arthritis (RA).Materials and Methods:An open-labeled randomized trial was conducted comparing 60,000 IU 1,25 dihydroxy vitamin D3 + calcium (1000 mg/day) combination [Group A] versus calcium (1000 mg/day) only [Group B], as supplement to existing treatment regimen in early RA. Primary outcome included (i) minimum time required for onset of pain relief (Tm) assessed through patients’ visual analog scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
2
13
0
2
Order By: Relevance
“…In a randomized interventional study on 73 RA patients with low DAS28 scores and vitamin D levels, a significant improvement in mean scores was seen with vitamin D supplementation over 3 months [ 43 ]. A randomized trial conducted in 150 patients from India concluded that weekly supplementation of 60,000 IU in early treatment-naïve RA patients resulted in greater pain relief [ 44 ]. In a meta-analysis of six RCTs with 438 participants, vitamin D complementary therapy resulted in more beneficial effects on DAS28, ESR.…”
Section: Vitamin D: Role In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized interventional study on 73 RA patients with low DAS28 scores and vitamin D levels, a significant improvement in mean scores was seen with vitamin D supplementation over 3 months [ 43 ]. A randomized trial conducted in 150 patients from India concluded that weekly supplementation of 60,000 IU in early treatment-naïve RA patients resulted in greater pain relief [ 44 ]. In a meta-analysis of six RCTs with 438 participants, vitamin D complementary therapy resulted in more beneficial effects on DAS28, ESR.…”
Section: Vitamin D: Role In Rheumatoid Arthritismentioning
confidence: 99%
“…D levels • No significant effect on RA symptoms measured as DAS28, CRP and VAS scores Effect of Vit D supplementation for pain relief in early RA, treatment-naïve (duration < 2 years) RA patients India 75 patients Two arms (along with DMARD therapy) Group A: Combination VitD3 (60,000 IU/week) + Calcium (1000 mg/day) Group B: Calcium (1000 mg/day) • After 8 weeks, Vit. D supplementation resulted in 50% higher pain relief and DAS-28 scores but not on the time required for the onset of pain relief (Tm) • Limited sample size [ 44 ] • Lack of placebo control • No Double Blinding • Vit. D deficiency is a risk factor for developing active RA Retrospective study to evaluate the clinical efficacy of Vit.D supplementation in RA patients China 1180 patients: VitD & Control Group • No significant change in primary efficacy & secondary efficacy outcomes was observed • Retrospective study [ 56 ] • Heterogeneity in the study population in terms of disease duration, activity & oral glucocorticoid A randomized, controlled trial to evaluate short term efficacy of Vit D supplementation on functional disability France 59 patients: 2 arms 29: VitD (100,000 IU) 30: Placebo/week for 6 months • Significant improvement in Health Assessment Questionnaire (HAQ) score • Small sample size [ 51 ] • No Vit.D assessment done after the end of the study • No difference in disease activity scores (DAS28ESR/DAS28CRP) The table summarizes the published clinical trial studies (Phases III & IV) on vitamin D. Details of associative and supplementation studies of vitamin D in Rheumatoid Arthritis are stated under different subheadings …”
Section: Vitamin D: Role In Rheumatoid Arthritismentioning
confidence: 99%
“…This is corroborated with studies demonstrating that decreased serum levels of D3 and O3FA are associated with increased disease activity in RA patients [ 15 , 16 ]. D3 insufficiency is known to promote inflammation and autoimmune responses [ 13 , 17 , 18 ]. Both D3 and O3FA are known to exert immunomodulatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…O3FA also blunts the polarization of Th-17 cells while enhancing the accumulation of Tregs, to skew immune responses towards an anti-inflammatory phenotype [ 21 ]. Aligned with these mechanistic studies, independent clinical studies of supplementation with either D3 or O3FA have demonstrated that these supplements can suppress the levels of circulating inflammatory mediators and modulate disease activity in RA [ 13 , 22 ]. Interestingly, a prospective study showed that increased dietary intake of both D3 and O3FA a year before DMARD initiation enhances treatment benefits, indicating a combinatorial effect of D3 and O3FA in patients with early RA [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinic, the immune regulation ability of RA patients is significantly related to the adjuvant treatment of 1,25(OH)2D3. 1,25(OH)2D3 supplement can relieve pain for RA patients ( 3 ) and the incidence of RA can be reduced after an increase of 1,25(OH)2D3 intake ( 4 ). The level of 1,25(OH)2D3 in serum is significantly higher in stable or mild RA patients than moderate and severe RA patients, revealing that the1,25(OH)2D3 level is closely associated to disease activity of RA ( 5 ).…”
Section: Introductionmentioning
confidence: 99%